A Study of Early Childhood Children Learning Behaviors through Experience Organized with Chinese Extracurricular Activities Base on a Blended Language Teaching Methodology TESSE - Kittachotworakul, Pongsathorn; Tang, Qiyuan (Journal of Human and Society, Sisaket Rajabhat University, 2023)
The objectives of this study were to 1) To study the development of the Kindergarten students studying through The Chinese Extracurricular Activities Base on a Blended language teaching methodology TESSE 2) To compare the development of learning experiences after studying through The Chinese Extracurricular Activities Base on a Blended language teaching methodology TESSE with The predetermined criteria. The Research Sample consisted of 24, selected by cluster random sampling, kindergarten 3/2 (K3/2) students of Tantrarak School, Chonburi province, in the academic year 1/2022. The research instruments were The Chinese Extracurricular Activities Base on a Blended Language Teaching methodology TESSE, a manual of the Chinese Extracurricular Activities Base on a Blended Language Teaching Methodology TESSE, learning experience plans, and a structured observation form Mean, percentage, standard deviation, efficiency, and t-test (one sample) were used for data analysis. The research results showed that 1) the learning behavior of students in every step according to the concept of the Blended Language Teaching Methodology TESSE was at a normal level, but the learning behavior of the goal-oriented aspect of the action phase was at an excellent level, and 2) the total average of learning behavior was higher than the specified standard (2.1) with a statistical significance at the .01 level.